Development of target‐tunable P22 VLP‐based delivery nanoplatforms using bacterial superglue. Issue 11 (1st August 2019) - Kim, Hansol; Choi, Hyukjun; Bae, Yoonji; Kang, Sebyung
Abstract: Protein cage nanoparticles are widely used as targeted delivery nanoplatforms, because they have well‐defined symmetric architectures, high biocompatibility, and enough plasticity to be modified to produce a range of different functionalities. Targeting peptides and ligands are often incorporated on the surface of protein cage nanoparticles. In this research, we adopted the SpyTag/SpyCatcher protein ligation system to covalently display target‐specific affibody molecules on the exterior surface of bacteriophage P22 virus‐like particles (VLP) and evaluated their modularity and efficacy of targeted delivery. We genetically introduced the 13 amino acid SpyTag peptide into the C‐terminus of the P22 capsid protein to construct a target‐tunable nanoplatform. We constructed two different SpyCatcher‐fused affibody molecules as targeting ligands, SC‐EGFRAfb and SC‐HER2Afb, which selectively bind to EGFR and HER2 surface markers, respectively. We produced target‐specific P22 VLP‐based delivery nanoplatforms for the target cell lines by selectively combining SpyTagged P22 VLP and SC‐fused affibody molecules. We confirmed its target‐switchable modularity through cell imaging and verified the target‐specific drug delivery efficacy of the affibody molecules displaying P22 VLP using cell viability assays. The P22 VLP‐based delivery nanoplatforms can be used as multifunctional delivery vehicles by ligating other functional proteins, as well as affibody molecules. The interior cavity of P22 VLP can be also used to load cargoes like enzymes and therapeutic proteins. We anticipate that the nanoplatforms will provide new opportunities for developing target‐specific functional protein delivery systems. Abstract : Protein cage nanoparticles are widely used as targeted delivery platforms due to their well‐defined symmetric structure and plastic enough to be modified with a range of different functionalities. Here, Kim and coworkers established P22 VLP‐based target‐tunable delivery nanoplatforms, adopted the SpyTag/SpyCatcher protein ligation system to covalently display two different target‐specific affibody molecules on their exterior on demand, and demonstrated their ligand and cargo modularity and high efficacy of targeted delivery of drugs toward their target cells.